Is vitamin D deficiency a risk factor in the occurrence and recurrence of febrile convulsions in children? - Thoppil, Joanne; Jyothirmayi, Chinta Annie; Arockiyaraj, Magdalenal; Mathew, Leni G.; Rebekkah, Grace; Mathai, Sarah (International Journal of Contemporary Pediatrics, 2024)
Background: Febrile seizure (FS) is the commonest childhood seizure. Our aim was to evaluate low Serum 25(OH) vitamin D level (vitamin D) as a risk factor for FS and whether vitamin D supplementation reduces its recurrence. Methods: A prospective cohort of children aged 6-60 months with FS (cases) and children with fever ≤3 days without seizures (controls) were recruited over a 2-year period. Vitamin D level was measured; those with low levels (<20 ng/ml) were treated with vitamin D for 3 months. Telephonic follow up was done upto 3 months regarding compliance, thereafter, upto 24 months for seizure recurrence. Results: 259 children (125 cases,134 controls) were recruited. Overall, 90 children (34.7%) had low vitamin D level. There was no difference between cases and controls with low vitamin D levels (p=0.37). 22 (17.6%) children had seizure recurrence. Of this serum vitamin D level was low in 2 (9.1%) while 20 (90.9%) had sufficient levels (p=0.021). The odds ratio for FS recurrence was 5.8 times higher among cases with normal vitamin D level (>20 ng/ml). Conclusions: There was no difference in mean vitamin D levels between cases and controls. However, there was significantly lower seizure recurrence in children who had low vitamin D level at presentation and had received vitamin D therapy. We postulate that treatment with vitamin D may reduce risk of FS recurrence even in those with serum vitamin D level in the “sufficient” range as per the recommended guidelines. Larger RCTs are needed to confirm these findings.